Relationship between PC index and magnetospheric field-aligned currents measured by Swarm satellites. (March 2018) - Troshichev, О.; Sormakov, D.; Behlke, R.
Abstract: The relationship between the magnetospheric field-aligned currents (FAC) monitored by the Swarm satellites and the magnetic activity PC index (which is a proxy of the solar wind energy incoming into the magnetosphere) is examined. It is shown that current intensities measured in the R1 and R2 FAC layers at the poleward and equtorward boundaries of the auroral oval are well correlated, the R2 currents being evidently secondary in relation to R1 currents and correlation in the dawn and dusk oval sectors being better than in the noon and night sectors. There is evident relationship between the PC index and the intensity of field-aligned currents in the R1 dawn and dusk layers: increase of FAC intensity in the course of substorm development is accompanied by increasing the PC index values. Correlation between PC and FAC intensities in the R2 dawn and dusk layers is also observed, but it is much weaker. No correlation is observed between PC and field-aligned currents in the midnight as well as in the noon sectors ahead of the substorm expansion phase. The results are indicative of the R1 field-aligned currents as a driver of the polar cap magnetic activity (PC index) and currents in the R2 layer. Highlights: The R1 and R2 FAC intensities in the dawn/dusk sectors are well correlated, the R2 currents being secondary relative to R1 currents. Increase of PC index in course of substorm growth phase follows the R1 FAC intensification in the dawn and dusk sectors. Correlation between R1 and R2 currents in the midnight and noon sectors is insignificant. Correlation between PC and R1FAC intensity in the midnight and noon is not found.